Tactile sensitivity of blind and visually impaired children and adolescents. The significance of swimming exercises - Rostkowska, Elżbieta; Maśnik, Elżbieta (Anthropological Review, 2001)
The aim of the study is to compare the tactile sensitivity threshold (TST) of the blind children who practice swimming and those who do not practice any sports with the TST of healthy people of similar age. TST was measured on the pad of the index finger of the dominant hand using an aesthesiometer. Lower TST was found in blind girls compared to healthy girls as well as lower TST in blind girls who practice swimming compared to the blind girls who do not practice any sports. A significant lowering of the TST during exercises in water was noted.